Trends for the Internationalization and Technification of Gulupa in Colombia: A Bibliometric Review with Bibliometrix - Escobar Quiñonez, Edward Enrique; Collazos Restrepo, Alexandra; García Molina, Gabriela (Universidad Francisco de Paula Santander, 2024)
This research focuses on examining the current patterns of global expansion and technological advancements of Gulupa (Passiflora ligularis Juss.) in Colombia through a bibliometric analysis using the Bibliometrix tool. Gulupa, commonly known as mountain granadilla, is an exotic fruit of considerable economic importance in Colombia, with growing interest in its penetration into foreign markets. The internationalization and technification of Gulupa in Colombia have been a subject of research interest due to the fruit's economic significance in the country. The bibliometric analysis highlights trends encompassing the identification of export markets, promotion and marketing strategies, as well as the challenges faced in the international expansion of this fruit. This quantitative examination provides a comprehensive overview of the most impactful topics and authors in this field. On the other hand, the technification of Gulupa production is essential to enhance quality and competitiveness in a globalized market. The bibliometric analysis examines research related to sustainable agricultural practices, cutting-edge technologies, and improvements in post-harvest processes. This reveals the growing emphasis on optimizing the Gulupa supply chain and implementing more efficient and sustainable practices. The results of this bibliometric analysis have significant implications for interested researchers, producers, and stakeholders in Gulupa production and marketing in Colombia. They identify areas of focus and prospects for future research, while also emphasizing the importance of technification in the fruit industry. Gulupa is emerging as a formidable contender in international markets, and the knowledge generated through this analysis can guide the development of future strategies for its promotion and sustainable growth.